San Clemente di Ocrida e la retorica biblica - Gjorgjevski, Gjoko; Meynet, Roland (Pontificia Universitas Gregoriana, 2017)
After a brief presentation of St Clement of Ohrid and the essential characteristics of biblical rhetoric, the three songs on the prefeast of Christmas composed by St Clement are studied according to the method of the analysis of biblical rhetoric. The first part deals with the composition: two of the songs are organized in a concentric manner, as often happens in biblical texts; instead, the other is of parallel composition. The second part deals with the context, which especially highlights the references to the scriptural texts. The final part is of interpretation to which the other two are directed: it consists of highlighting the articulations of the text, i.e. the movement in which it is animated.
Keywords: St. Clement of Ohrid, songs of the prefeast of Chrismas, biblical and semitic rhetoric